Immunocytochemistry associated with oral exfoliative cytology: Methodological analysis - da Silva, Alessandra Dutra; Lima, Celina Faig [UNESP]; Maraschin, Bruna Jalfim; Laureano, Natália Koerich; Daroit, Natália Batista; Brochier, Fernanda; Sant'Ana Filho, Manoel; Visioli, Fernanda; Rados, Pantelis Varvaki (My University, 2015)
Objective: To evaluate different immunocytochemical protocol variations to find the most effective protocol for the analysis of involucrin, epidermal growth factor receptor (EGFR), and E-cadherin antibodies. Exfoliative cytology is a noninvasive method used to monitor and screen for early changes in the oral mucosa of patients exposed to carcinogens such as tobacco and alcohol. It has been postulated that its association with immunocytochemistry may improve the effectiveness of the screening process. Study Design: Four graduate students from Porto Alegre in southern Brazil had oral smears collected from the border of the tongue using a cytobrush. The following variables were analyzed: cell membrane permeability, antigen retrieval method (microwave oven or water bath), antibody incubation time (overnight or 1 hour), detection system used (Envision or LSAB), and chromogen incubation time (10 seconds or 5 minutes). Results: Best results were obtained with the following combinations: (1) for involucrin: water bath, 1-hour incubation for primary antibody, Envision, and chromogen incubation for 10 seconds; (2) for EGFR: microwave, overnight incubation, LSAB, and chromogen incubation for 5 minutes; and (3) for E-cadherin: water bath, overnight incubation, Envision, and chromogen incubation for 5 minutes. Conclusion: Our findings suggest that each antibody requires a specific immunocytochemical protocol to guarantee optimal results with oral smears.
Keywords: E-cadherin antibodies; Epidermal growth factor receptor (EGFR); Exfoliative cytology; Immunocytochemistry; Involucrin; Oral cytopathology; Oral exfoliative cytology; Oral smears